Contramapeo en escritoras contemporáneas en espanol - Noguerol Jiménez, Francisca (Verba hispanica, 2024)
This article highlights how two relevant contemporary titles – Canción de antiguos amantes (2022) by the Colombian Laura Restrepo and Palestina en pedazos(2021) by the Chilean Lina Meruane – denounce the “moralblindness” characteristic of our times. These texts carry out a countermapping of power by attending to spaces marked by endemic violence:Yemen, Ethiopia, Somalia and Palestine. Both of them utilize “forensic writing” and pay special attention to myth (Restrepo) and autoethnography (Meruane)
Keywords: autoethnography; avtoetnografija; countermapping; Latin American literature; latinoameriška književnost; Meruane, Lina; mit; myth; proti-kartiranje; Restrepo, Laura